Isolation of atypical mycobacteria from tonsils and lymph nodes of bovines - Langenegger, Charlotte Hubinger; Langenegger, Jerome (Pesquisa Agropecuaria Brasileira, 2014)
Twenty nine atypical mycobacteria belonging to the Runyon, groups II and III, have been isolated from the tonsils and the mandibular, parotid and retropharyngeal lymph nodes of 19 (21.5%) out of 88 normal slaughtered bovines. One strain of Mycobacterium avium, 3 of M. scrofulaceum, 2 of M. gordonae, 4 of M. intracellulare and 5 of M. terrae complex, were identified from the tonsils. One strain of M. avium, 6 of M. scrofulaceum, 1 of M. gordonae, 1 of M. xenopi, 1 of M. intracellulare and 4 of M. terrae complex, were identified from the lymph nodes. Some of these cultures when inoculated, intradermally into guinea pigs (0.1 mg/humid weight) caused ulceration of the skin, and when inoculated by intramuscular injection (1 mg/humid weight) caused local abscess formation. Some of the M. scrofulaceum, M. gordonae, and M. xenopi strains inoculated intradermally, (2 mg/humid weight) into swine produced ulceration of the skin and metastatic lesions in the regional lymph node.